THE EFFECT OF THE ABILITY IN MASTERING DIALOGUE AND MOTIVATION TOWARDS STUDENT’S ENGLISH LEARNING ACHIEVEMENT At SMA AL-Kholidiyah Karawang - Asep Darojatul Romli (Universitas Buana Perjuangan Karawang, 2018)
ABSTRACT The effect of the ability in mastering dialogue on motivation, to know and explain the effect of the ability in mastering dialogue on English learning achievement, to know and explain the effectof motivation ability on English learning achievement and to know and explain the effectof the ability in mastering dialogue on learning achievement English through motivation. The research method used is survey method. Population in this research is all students of class X of first semester of SMA AL-Kholidiyah, Karawang. The sampling technique used is cluster random sampling, the sample is taken randomly according to the class that has been formed. So, the sample in this study as many as 18 people from the total population of 192 people. The research instrument consists of three types of tests, namely the questionnaire of the ability in mastering dialogue , motivation and English achievement test with the subject of the circle. Analysis of statistical data to test the hypothesis in this study using Path Analysis (Path Analysis). Statistic test is used t test. The results showed: (1) direct effectof the ability in mastering dialogue on motivation, (2) direct effectof the ability in mastering dialogue on English learning achievement, (3) direct effectof the ability in mastering dialogue to English learning achievement and (4) indirect effect of lateral thinking ability toward English learning achievement through creative thinking ability. Keywords: The ability in mastering dialogue, Motivation and English learning achievement